The Impact of Supplier Development Practices of Retailers and Buyer-Supplier Relationship on the Performance of Suppliers in the Clothing Industry in Sri Lanka - De Silva, H.L.M.; Jayarathne, P.G.S.A. (My University, 2018)
Attached